Shear Force–Displacement Curve of a Steel Shear Wall Considering Compression - Yi Liu; Yan He; Yang Lv (Buildings, 2025)
The shear strength of a steel shear wall (SSW) is typically governed by the yield strength of the steel. However, changes in mechanical properties beyond yielding—particularly those related to steel hardening and the effects of gravity loads—are not yet fully understood. These factors are critical for accurately assessing the shear capacity of SSWs during seismic events. In the current study, a method to calculate the shear force–displacement curve of a steel shear wall while considering the compression effect is presented, which incorporates both steel hardening and gravity effects. The analysis derives strains in tensile strips undergoing shear deformation using a strip model. Corresponding stresses are then determined using the stress–strain relationships obtained from tensile tests of the steel. Furthermore, the vertical stress induced by gravity loads is modeled using a three-segment distribution proposed before. For each tensile strip, the tension field stress is calculated by accounting for reductions due to vertical stress and the influence of steel hardening through the von Mises yield criterion. This approach enables the development of a shear force–displacement curve, which is subsequently validated against results from an experimentally verified finite element model. The findings demonstrate that the pushover curves predicted by this method closely align with those obtained from finite element analysis. Notably, the results indicate that the shear strength provided by the CAN/CSA-S16-01 equation may be overestimated by approximately 4%, 9%, and 18% when the vertical compression stresses are 50, 100, and 150 MPa for a wall with a slenderness of 150, respectively.